2018
DOI: 10.1530/jme-17-0183
|View full text |Cite
|
Sign up to set email alerts
|

miR-20a-5p promotes adipogenic differentiation of murine bone marrow stromal cells via targeting Kruppel-like factor 3

Abstract: miR-20a-5p has recently been identified to induce adipogenesis of established adipogenic cell lines in our previous study. However, its role and molecular mechanisms in the regulation of adipocyte lineage commitment of bone marrow-derived stromal cells (BMSCs) still need to be explored. In this report, we demonstrated the expression of miR-20a-5p was promoted gradually during adipogenic differentiation in BMSCs. We also confirmed that miR-20a-5p has a positive function in the adipogenic differentiation of BMSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Kdm6b, Tgfbr2 and Klf3 have been demonstrated to be the direct targets of miR-20a-5p in our previous studies (21,22). In this study, Tob2 was predicted to be a potential target of miR-20a-5p and the potential pairing between miR-20a-5p and Tob2 is shown in Figure 5A.…”
Section: Tob2 Was a Direct Target Gene Of Mir-20a-5psupporting
confidence: 54%
See 2 more Smart Citations
“…Kdm6b, Tgfbr2 and Klf3 have been demonstrated to be the direct targets of miR-20a-5p in our previous studies (21,22). In this study, Tob2 was predicted to be a potential target of miR-20a-5p and the potential pairing between miR-20a-5p and Tob2 is shown in Figure 5A.…”
Section: Tob2 Was a Direct Target Gene Of Mir-20a-5psupporting
confidence: 54%
“…In addition, the miR-20a-5p sponge lentivirus (Sponge LV) were made according to previously published protocol (22). Oil-red O staining showed that the sponge LV infection resulted in fewer differentiated adipocytes and less triglyceride content as compared with control LV (Figures 4A,B).…”
Section: Mir-20a-5p Regulated Adipocyte Differentiation and Lipogenesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, miR-34a, miR-450a-5p, and miR-28- 5p have been revealed to be involved in regulating the osteoblastic differentiation of mesenchymal stem cells [38,39]. In BMSCs, the adipogenic and osteogenic differentiation can also be regulated by miR-383 [40], miR-20a-5p [41], and miR-20a-5p [41]. Moreover, some miRNAs are reported to be involved in the development of SANFH.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from cells using a total RNA isolation kit (Omega Bio-Tek, Norcross, GA, USA), and 0.5 mg RNA of each sample was reverse-transcribed to cDNA with a Reverse Transcription Kit (Thermo Fisher Scientific, Shanghai, China). Quantitative PCR (qPCR) analyses for the mRNA expression were performed as previously described (27) by using TransStart Green qPCR SuperMix (TransGen Biotech, Beijing, China) on the Light Cycler 96 Real-Time PCR System (Roche Diagnostics, Mannheim, Germany). The relative expression levels of the target genes were calculated using the comparative threshold cycle method (28).…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%